Sex Work in Contemporary Russia: A Cultural Perspective - Schuckman Matthews, Emily (Lexington Books, 2023)
Sex Work in Russia weaves together a wide range of materials to examine the figure of the female sex worker in Russia from the early twentieth century to the present day. This book offers readers both an expansive and nuanced discussion of the significance of this archetypal female who appears with remarkable frequency in literature, film, and other cultural productions. Emily Schuckman Matthews explores the ways in which the fictional sex worker (and her real-life counterpart) has become a symbolic representative of social and moral instability, economic volatility, political, social, and ideological revolutions, and changing concepts of gender, sexuality, and the nation itself. Focus is given to the movement of the female sex worker from marginal foil to a hero in her own right, even finding a voice of her own in recent years. Works featuring this alluring and complex figure reveal critical insights into the changing position of women and other marginalized people in a volatile Russia.